Effectiveness of Interventions to Improve Preceptor Performance in Nursing Student Competencies - Ummi Kulsum; Rizki Fitryasari; Nuzul Qur’aniati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Perceptors need to be proficient in clinical teaching and assessment in reaching learning objectives while handling client caseload and delivering safe and efficient care. However, evidence to inform best practices for mentor development is limited, as is evidence regarding the efficacy of programs for the mentor role. This study aims to analyse interventions to improve preceptor performance on nursing student competencies. Methods: This study employs a systematic review, with study literature gathered from multiple electronic databases, including Pubmed, Science Direct, ProQuest, and SAGE using a PRISMA flow guidline. Data was collected by searching for research for 2019-2024 and searches were conducted until March 4, 2024. The keywords used are